The Value of a Genetic Counselor: Improving Identification of Cancer Genetic Counseling Patients with Chart Review. Issue 3 (25th October 2013) - Eichmeyer, Jennifer N.; Burnham, Christa; Sproat, Patty; Tivis, Rick; Beck, Thomas M.
Abstract: Advances in genetics are changing cancer care and requiring institutions to maximize the unique skills of genetics professionals. The identification of genetic syndromes is vital for prevention and management of families with high cancer risks. Despite this, high risk individuals who qualify are often not referred. Genetic counselors could review oncology charts to improve identification. A genetics assessment tool developed by NCI Community Cancer Centers Program was used to perform self‐assessment of the genetics program. A weekly report of all new oncology patients was provided to a genetic counselor for chart review. In 2010, 58 % of all eligible patients ( n  = 152) were offered a genetics evaluation. In 2011 this improved to 70 % ( n  = 167), which was a statistically significant difference, X 2 (1) = 5.13, p  = 0.02. By cancer site, ovarian cancer referrals also showed statistically significant improvement, X 2 (1) = 6.36, p  = 0.01. Breast and colon referrals were improved but not significant. Over 10 months, 129 patients were identified through the chart review program. Three were confirmed to have a genetic mutation for a hereditary cancer syndrome. An average week included review of 73 charts for 10 medical oncologists, 4 radiation oncologists, and 4 pediatric oncologists which generated 60–80 min of work for the genetic counselor. This program improved patient identification and quality, and allowed physicians to become more aware of opportunities for genetic counseling and more patients to receive genetic counseling and testing.